A CRISPR New World: Attitudes in the Public toward Innovations in Human Genetic Modification - Weisberg, Steven M.; Badgio, Daniel; Chatterjee, Anjan (Frontiers in Public Health, 2017)
The potential to genetically modify human germlines has reached a critical tipping point with recent applications of CRISPR-Cas9. Even as researchers, clinicians, and ethicists weigh the scientific and ethical repercussions of these advances, we know virtually nothing about public attitudes on the topic. Understanding such attitudes will be critical to determining the degree of broad support there might be for any public policy or regulation developed for genetic modification research. To fill this gap, we gave an online survey to a large (2493 subjects) and diverse sample of Americans. Respondents supported genetic modification research, although demographic variables influenced this attitudes– conservatives, women, African Americans, and older respondents, while supportive, were more cautious than liberals, men, other ethnicities, and younger respondents., Support was also was slightly muted when the risks (unanticipated mutations and possibility of eugenics) were made explicit. The information about genetic modification was also presented as contrasting vignettes, using one of five frames: genetic editing, engineering, hacking, modification, or surgery. Despite the fact that the media and academic use of frames describing the technology varies, these frames did not influence people’s attitudes. These data contribute a current snapshot of public attitudes to inform policy with regard to human genetic modification.